2014
DOI: 10.1007/s00216-014-8135-7
|View full text |Cite|
|
Sign up to set email alerts
|

Lateral resolution of nanoscaled images delivered by surface-analytical instruments: application of the BAM-L200 certified reference material and related ISO standards

Abstract: The certified reference material BAM-L200, a nanoscale stripe pattern for length calibration and specification of lateral resolution, is described. BAM-L200 is prepared from a cross-sectioned epitaxially grown layer stack of AlxGa1-xAs and InxGa1-xAs on a GaAs substrate. The surface of BAM-L200 provides a flat pattern with stripe widths ranging down to 1 nm. Calibration distances, grating periods and stripe widths have been certified by TEM with traceability to the length unit. The combination of gratings, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…In order to test and evaluate the advances in these instruments with respect to spatial resolution, both the appropriate resolution reference materials and unbiased procedures to evaluate the quality of the images produced are required. As the spatial resolution of these technologies has begun to reach into the nanometer regime, finding readily available or easily made resolution reference materials has become particularly challenging for both elemental and molecular imaging purposes …”
mentioning
confidence: 99%
“…In order to test and evaluate the advances in these instruments with respect to spatial resolution, both the appropriate resolution reference materials and unbiased procedures to evaluate the quality of the images produced are required. As the spatial resolution of these technologies has begun to reach into the nanometer regime, finding readily available or easily made resolution reference materials has become particularly challenging for both elemental and molecular imaging purposes …”
mentioning
confidence: 99%
“…Fig. 4 shows a result when a (color online) Layout and design of the certified reference material BAM L200 for imaging AES and SIMS instruments [8].…”
Section: How We Can Implement the Classical Definition To Imaging Surmentioning
confidence: 99%
“…3 and ref. [8]) is available in the Web Shop of BAM at www.bam.de. Therefore, I think it is worth to be published from JSA .…”
Section: Donementioning
confidence: 99%
“…One of the few examples is the reference sample BAM-L200, a material with stripe structures of certified dimensions in the nano-range, specially designed for testing the spatial resolution of imaging micro/nano-probe techniques. This material has been prepared as a FIB lamella [4] and it was demonstrated that spatial resolutions of the EDX signals in the range of a few nm can be achieved.The need for and the availability of automatic image acquisition (including spectral information) with the goal of automatic chemical classification will be discussed. The coupled automatic data evaluation will be also addressed by some practical examples.…”
mentioning
confidence: 99%
“…One of the few examples is the reference sample BAM-L200, a material with stripe structures of certified dimensions in the nano-range, specially designed for testing the spatial resolution of imaging micro/nano-probe techniques. This material has been prepared as a FIB lamella [4] and it was demonstrated that spatial resolutions of the EDX signals in the range of a few nm can be achieved.…”
mentioning
confidence: 99%